T cells, B cells, and PD-L1 expression in esophageal and gastric adenocarcinoma before and after neoadjuvant chemotherapy: relationship with histopathological response and survival. (1st January 2021) - Christina Svensson, Maria; Lindén, Albin; Nygaard, Jakob; Borg, David; Hedner, Charlotta; Nodin, Björn; Leandersson, Karin; Jirström, Karin
ABSTRACT: Perioperative chemotherapy enhances the survival rates for patients with esophageal and gastric (EG) adenocarcinoma, but not all patients benefit from this additional treatment. Chemotherapeutic agents have been demonstrated to alter the immune cell (IC) composition in the tumor microenvironment. Hence, there is a rationale to investigate the influence of neoadjuvant chemotherapy (NAC) on different IC subsets, to better understand and compare their utility as complementary prognostic or predictive biomarkers in a clinically relevant context. The density of T cells (CD8 + and FoxP3 + ), B cells (CD20 + ) and the expression of PD-L1 on ICs and tumor cells (TC) was assessed by immunohistochemistry on paired biopsies from primary tumors (PT) pre-NAC, and resected PT and lymph node metastases post-NAC. The cohort encompasses 148 patients with resectable EG adenocarcinoma, all of whom received NAC. The density of CD8 + cells was decreased and the density of FoxP3 + cells and CD20 + cells was increased in PT post-NAC. PD-L1 expression was not altered following NAC. In pre-NAC specimens, high FoxP3 + density and high PD-L1 expression on ICs were favorable prognostic factors, whereas high CD8 + density was an unfavorable prognostic factor. In post-NAC specimens, however, high FoxP3 + density was an unfavorable prognostic factor, and high PD-L1 expression on TC was associated with a shorter survival. There were no significant associations between IC density or PD-L1 expression in PT pre-NAC and histopathological regression. These findings propose that NAC might alter the density and prognostic impact of some IC subsets in EG adenocarcinoma.